2014
DOI: 10.1021/ie403052m
|View full text |Cite
|
Sign up to set email alerts
|

Photo-, Bio-, and Magneto-active Colored Polyester Fabric with Hydrophobic/Hydrophilic and Enhanced Mechanical Properties through Synthesis of TiO2/Fe3O4/Ag Nanocomposite

Abstract: A polyester fabric with durable photo-, bio-, and magneto-activities was prepared in a single-step process. In the proposed method alkali hydrolysis of polyester fabric was carried out along with the synthesis of the TiO 2 /Fe 3 O 4 /Ag nanocomposite, which enhanced the surface activity and nanoparticles adsorption, and produced ethylene glycol for reducing silver nitrate into nano-silver. The uniform distribution of the nanocomposite on the fiber surface was confirmed by FESEM and EDX. The fabrics showed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Copper and copper oxide nanoparticles have been synthesized on different fabrics creating antibacterial, conductivity and chemical sensing properties [48,49]. Iron oxide nanoparticles and TiO 2 /Ag/iron oxide nanocomposites have been in-situ synthesized on polyester fabric producing magneto, photo, bio-active textiles [50][51][52]. In addition, use of sonochemistry as a new route for in-situ deposition of nanoparticles onto textile substrates has recently been of increasing interest [53].…”
Section: Nano-finishingmentioning
confidence: 99%
“…Copper and copper oxide nanoparticles have been synthesized on different fabrics creating antibacterial, conductivity and chemical sensing properties [48,49]. Iron oxide nanoparticles and TiO 2 /Ag/iron oxide nanocomposites have been in-situ synthesized on polyester fabric producing magneto, photo, bio-active textiles [50][51][52]. In addition, use of sonochemistry as a new route for in-situ deposition of nanoparticles onto textile substrates has recently been of increasing interest [53].…”
Section: Nano-finishingmentioning
confidence: 99%
“…In comparison with the control sample with water spreading time of 3 s, all the ZnO treated samples had higher water spreading time before sunlight irradiation (Table 1), indicating more hydrophobic surfaces. This arises from the in-situ synthesis of zinc oxide nanoparticles on polyester surface and the air bubbles trapped in the rough surface of such coatings [2,3]. On the other hand, the control-aminolyzed sample at TEA concentration of 0.11% v/v was hydrophilic with water spreading time reduced to 0.7 s. The amine functional groups introduced on the polyester surface during aminolysis have been proved to enhance the hydrophilic property [1,13].…”
Section: Wettabilitymentioning
confidence: 99%
“…Introducing specific functional groups on polyester surface to improve the performance and obtain new applications has been always demanded [2][3][4]. It has been suggested that surface modification affect handle, thermal properties, permeability, and hydrophilicity of polyester fibers [1].…”
Section: Introductionmentioning
confidence: 99%
“…28 Damage to the lipids, proteins and DNA of the microorganisms are the main antibacterial mechanisms of silver nanoparticles. 29 A fabric was also treated with 0.11% v/v triethanolamine alone with the same conditions with an antibacterial efficiency of $99.99% against both Staphylococcus aureus and Escherichia coli bacteria. The antibacterial activity of polyols has been reported in literature to be related to the hydrophilic nature of the polyols, which causes the desiccating of the microbes, depriving the bacteria the required moisture and/or absorbing resulted in dispersing the bacteria membrane.…”
Section: Antibacterial Efficiencymentioning
confidence: 99%